Impact of pre-hospital electrocardiogram teletransmission on time delays in ST segment elevation myocardial infarction patients: a single-centre experience - Zimoch, Wojciech J.; Kosowski, Michał; Tomasiewicz, Brunon; Langner, Anna; Kubler, Piotr; Jankowska, Ewa A.; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Delay in diagnosis and treatment has a great influence on morbidity and mortality of ST-segment elevation myocardial infarction (STEMI) patients. Every 30 min of delay in reperfusion is associated with an 8% increase in mortality. ECG teletransmission was proved to effectively shorten time delays in STEMI treatment. In 2012 an ECG teletransmission program was introduced in the Lower Silesia region. Aim : To assess the frequency of ECG teletransmission in STEMI patients and its influence on time delays. Material and methods : We conducted a retrospective analysis of all patients admitted to our hospital with STEMI in 2013. Time delays, treatment and clinical characteristics of patients with and without teletransmission performed were compared. Results : The study included 137 patients, of whom 49 (36%) had teletransmission performed. Direct transport to a percutaneous coronary intervention (PCI)-capable hospital was more frequent in patients with ECG teletransmission performed (88% vs. 63%, p = 0.002). In patients with teletransmission pain-emergency room time and total ischemic time were shorter (respectively 125 (91–184) min vs. 201 (113–339) min, p = 0.001 and 159 (136–244) min vs. 259 (170–389) min, p < 0.001). There were no differences in in-hospital delay, patients’ characteristics, or applied therapy. Conclusions : The percentage of STEMI patients who had ECG teletransmission performed was low. Patients with ECG teletransmission had a shorter total ischemic time and lower percentage of indirect transport to a PCI-capable hospital.